The 2016 ENFSI Fingerprint Working Group testing programme. (November 2018) - Zampa, F.; Fish, J.; Hilgert, M.; Lövby, T.; Svensson, M.; Vaughan, J.; Mattei, A.
Highlights: Two collaborative exercises were carried out in 2016 within ENFSI EFP-WG. Visualisation Test (V-CE) was focused on adhesive tape removal. V-CE: the use of solvents provided to be successful to make removal easier. V-CE: indications about a rational approach to this kind of item are given. Comparison Proficiency Test: verified easiness of the test. Abstract: In 2016, the Fingerprint Working Group (EFP-WG) of the European Network of Forensic Science Institutes (ENFSI), officially established an advisory group with the task of organising proficiency tests (PTs), as well as collaborative exercises (CEs) as a way of raising standards within the fingerprint profession. This article will provide an overview of the Visualisation collaborative exercise and the Comparison proficiency test, which were carried out in 2016. Both the exercise and the test were organised and co-funded by the Prevention of and Fight against Crime Programme of the European Union[1–3], Direct Grant "Towards the Vision for European Forensic Science 2020 (TVEFS-2020)" HOME/2013/ISEC/MO/ENFSI/4000005962, work package T3 "Proficiency Tests and Collaborative Exercises for the Fingerprint Domain" . The characteristics of the testing programme are summarised, followed by an overview of the knowledge that has been gained, including lessons learnt.